HUMAN RIGHTS, THE CHURCH’S MISSION AND INCULTURATION - Gascoigne, Robert (Asian Horizons, 2011)
Since Vatican II, and especially because of the pontificate of John Paul II, support for human rights, both locally and globally, has become a key aspect of the life and mission of the Church. It is now clearly part of the mission of the Church to communicate a concern and demonstrate practical support for human rights. Yet, in order to be effective and truly evangelizing, this concern for human rights must be communicated by and through local churches in ways that are relevant to the communities they serve, their national and cultural contexts. In keeping with the focus of this issue of Asian Horizons, this essay will focus on the question of inculturation in relation to the Church’s proclamation of and support for human rights. The purpose of this essay is to consider some aspects of the inculturation of the Church’s mission on behalf of human rights, in particular to consider how reflection on the inculturation process can reveal some of the features of this mission and make them more explicit. Its focus will be on my own Australian context, as a particular example of inculturation, but it will also draw some more general conclusions about the task of inculturation. Reference will be made to Australian sources for particular points of context, but also to more general works on human rights, in order to make connections with more general concerns in the interpretation and inculturation of human rights.